Categories of race: technologies of knowing and governing Australian aborigines†. Issue 14 (13th November 2016) - McCallum, David
ABSTRACT: This article documents the first decades of the work of the Aboriginal Protection Board in Victoria, Australia in the mid-nineteenth century, as it oversees the establishment of mission stations to gather up Aboriginal peoples and provide protection from settler violence. It augments existing accounts of white settler governance of Aboriginal peoples by examining the social and historical conditions for the emergence of separations and distinctions between Aboriginal peoples through shifting governmental versions of the 'Aboriginal problem'. The production of race-based categories of persons is highlighted in the State's management of the Aboriginal children through the mission systems and their effects on Aboriginal ties to community and identity.